Pancreaticoureteric fistula following penetrating abdominal trauma: A Case Report - Hamza Bashir; Nouman , Muhammad; Khan, Muhammad Arsalan (Journal of the Pakistan Medical Association, 2024)
Pancreaticoureteric Fistula (PUF) is a very rare complication secondary to penetrating abdominal trauma involving the ureter and pancreatic parenchyma. Pancreatic injuries carry high morbidity due to the involvement of surrounding structures and are difficult to diagnose due to their retroperitoneal location. A case of a patient is reported at Civil Hospital, Hyderabad who presented with a history of firearm injury and missed pancreatic duct involvement on initial exploration that eventually led to the development of Pancreaticoureteric Fistula. He was managed via percutaneous nephrostomy (PCN) for the right ureteric injury and pancreatic duct (PD) stenting was done for distal main pancreatic duct injury (MPD). Key Words: Pancreatic injury, Pancreaticoureteric Fistula, Penetrating abdominal trauma.